Jam Rock Music Center - Pangilinan, Rustum R. (Manila : National University, 2014)
Jam Rock Music Center builds to have a place where all rock music artists, music enthusiasts, bands, and viewers can express themselves to the world and to show their great talent especially to our Filipino artists. Jam Rock Music Center offer musical instrument tutorials where they teach guitar, bass, keyboard, drums, and voice lesson and a live performance for the student after they finish the program levels. It has recording and band rehearsal studios, a museum that will educate not only those who love rock music but also all the people, by inspiring them through showing those instruments used by great artist, inspirational quotes in life, tracks, action figures, the evolution of rock music from when it started up to the present day, how these music change the way of life of a person, how rock music can change the world. It also has a concert ground which will serve as the main venue for rock concert in the Philippines, to have a proper place, a proper home for those artist, by uniting them through this music center and to create family. To provide facilities which the existing concert ground doesn't have, Jam Rock Music Center will promote the Architecture and its inspirational concept. One of the reasons of building Jam Rock Music Center is to endorse our very own ROCK MUSIC CENTER nationwide.
Chapter 1. The problem and its setting -- Chapter 2. Research methodology -- Chapter 3. Terms of references -- Chapter 4. Data gathering, collation and analysis of data -- Chapter 5. Design framework -- Chapter 6. Translations -- Chapter 7. Revisions, suggestions, and comments -- Annexes.
Includes bibliographical references.
Keywords: MUSIC CENTER